Is theological neutrality the final word in interreligious dialogue? - Rambachan, Anantanand (Dialog, 2019)
This article offers a response to the ELCA Declaration of Interreligious Commitment from a Hindu perspective. It raises important questions, and presses Lutherans on the issue of evangelism.